Media's Influence on Body Shaming: Its Effect on the Self-Confidence of Grade 12 HUMSS Students at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Education plays a big role in a person's success and efficiency. Education made the community and society strong in many matters. In this digital era where people are on social media bases, especially students, one of the affecting factors in their academic performance is Body Shaming. This was a big issue, especially for those who experienced body shaming. The research design applied in this was the Qualitative Research Method; we generated data by using Google Forms to survey our classmates and batchmates at Bestlink College of the Philippines. The sampling technique generated in this research study was the random sampling technique, wherein we chose our respondents randomly and assumed they experienced Media Body Shaming. According to the data we gathered, the students are affected by Media Body Shaming from their academic task perspective. The students lost their confidence and daily normal routine, especially in school. They were shy about participating in class. That causes bad grades and low scores in the activities and quizzes. The objective of this study was to be an eye opener to everybody, especially parents and teachers, to be aware of the mental condition of their students and children.
Keywords: Body Shaming; Academic Performance; Mental Health; BCP